2008
DOI: 10.1186/1471-2377-8-45
|View full text |Cite
|
Sign up to set email alerts
|

Plasma brain natriuretic peptide as a surrogate marker for cardioembolic stroke

Abstract: Background: Cardioembolic stroke generally results in more severe disability, since it typically has a larger ischemic area than the other types of ischemic stroke. However, it is difficult to differentiate cardioembolic stroke from non-cardioembolic stroke (atherothrombotic stroke and lacunar stroke). In this study, we evaluated the levels of plasma brain natriuretic peptide in acute ischemic stroke patients with cardioembolic stroke or non-cardioembolic stroke, and assessed the prediction factors of plasma b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
3
13
1
Order By: Relevance
“…The prevalence of elevated BNP levels was low in other stroke subtypes (20%), a finding consistent with the previously published studies. 19,21,26 Almost three fourths of cardioembolic stroke patients in our study had high BNP, which is comparable to the study by Yukiiri et al 21 among Japanese cardioembolic stroke patients and Montaner et al 27 in Spanish patients. We did not find any association between elevated BNP and noncardioembolic strokes; our findings advocated other studies.…”
Section: Stroke Subtypessupporting
confidence: 93%
“…The prevalence of elevated BNP levels was low in other stroke subtypes (20%), a finding consistent with the previously published studies. 19,21,26 Almost three fourths of cardioembolic stroke patients in our study had high BNP, which is comparable to the study by Yukiiri et al 21 among Japanese cardioembolic stroke patients and Montaner et al 27 in Spanish patients. We did not find any association between elevated BNP and noncardioembolic strokes; our findings advocated other studies.…”
Section: Stroke Subtypessupporting
confidence: 93%
“…In a previous study, we reported that a BNP level >140.0 pg/ml could discriminate CE from non-CE patients, which was incompatible with findings from other studies [5,6]. Montaner et al [5] demonstrated that the optimal cutoff point of BNP to distinguish between CE and non-CE was 76 pg/ml, which corresponded with a sensitivity of 72% and specificity of 68% [10].…”
Section: Discussioncontrasting
confidence: 44%
“…Montaner et al [5] demonstrated that the optimal cutoff point of BNP to distinguish between CE and non-CE was 76 pg/ml, which corresponded with a sensitivity of 72% and specificity of 68% [10]. Similarly, Yukiiri et al [6] reported that the optimal cutoff point of BNP to distinguish between CE and non-CE was 77 pg/ml, which corresponded with a sensitivity of 75.8% and a specificity of 76.8%. The reason for this discrepancy between the present study and these previous studies may be attributed to various factors, including differences in the study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated measurement of hs-CRP levels and mean hs-CRP levels could help to clarify the interrelationship. Yukiiri et al described the predictive value of plasma BNP according to the subtype of ischemic stroke in non-ESRD populations [25]. They reported that plasma BNP can be a surrogate marker for cardioembolic stroke and can differentiate cardioembolic stroke from other types of stroke.…”
Section: Discussionmentioning
confidence: 98%